2021
DOI: 10.1007/s11051-020-05137-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of mechanical properties of aluminum-copper alloys at nanoscale

Abstract: Nanoindentation is a powerful tool capable of providing fundamental insights of material elastic and plastic response at the nanoscale. Alloys at nanoscale are particularly interesting as the local heterogeneity and deformation mechanism revealed by atomistic study offers a better way to understand hardening mechanism to build a stronger material. In this work, nanoindentation in Al-Mg alloys are studied using atomistic simulations to investigate the effects of loading direction, alloying percentages of Mg via… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…On the other hand, molecular dynamics simulation of the Cu-Sb alloy shows that the formation of unstable stacking faults near the solute atoms leads to the softening of the alloy [8,9]. It has also been reported that the addition of aluminum as a solid solution in the copper structure makes the cross slip during the deformation easier, which causes the work hardening to be dependent on the strain rate [10,11]. In the study of copper alloy deformation, Szczerba et al [12] emphasized the dual role of material stacking fault energy on the activation of twinning and twinning stress of face-centered cubic (FCC) materials.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, molecular dynamics simulation of the Cu-Sb alloy shows that the formation of unstable stacking faults near the solute atoms leads to the softening of the alloy [8,9]. It has also been reported that the addition of aluminum as a solid solution in the copper structure makes the cross slip during the deformation easier, which causes the work hardening to be dependent on the strain rate [10,11]. In the study of copper alloy deformation, Szczerba et al [12] emphasized the dual role of material stacking fault energy on the activation of twinning and twinning stress of face-centered cubic (FCC) materials.…”
Section: Introductionmentioning
confidence: 99%
“…The increased strength results in the seriously decreased plasticity and machinability with the addition of the particles into the matrix alloys. The ductility is maintained or increased of the AMCs when the particles decrease to nano-size [17][18][19][20]. However, the nano-sized particles are difficult to distribute homogeneously in Al-matrix [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%